Fatal consequences of decreased sensitivity to pain and temperature in a frontotemporal dementia patient. Issue 6 (1st November 2020) - Martínez Dubarbie, F.; López-García, S.; Andrés-Gómez, M.; Lage, C.; Pozueta, A.; García-Martínez, M.; Kazimierczak, M.; Bravo, M.; Jiménez-Bonilla, J.; Banzo, I.; Rodríguez-Rodríguez, E.; Sánchez-Juan, P.
ABSTRACT: Frontotemporal dementia (FTD) is a heterogeneous syndrome characterized by the progressive damage of frontal and temporal brain regions. These networks largely overlap with those involved in pain and temperature processing. Although the impaired perception of pain and temperature has been previously described to be relatively common in patients with FTD, these symptoms are often not consistently assessed by Neurologists. We present the case of a patient with a probable behavioral variant FTD who died due to scalding with hot water in the shower. Impairments in the perception of pain and temperature might have played a fundamental role in this accident.